Influence of nitrogen fertilizer dose on false smut of rice (Oryza sativa) caused by Ustilaginoidea virens - RANI, RITU; SHARMA, VINEET K; PANNU, P P S; LORE, JAGJEET S (The Indian Journal of Agricultural Sciences, 2015)
The effects of five nitrogen fertilizer doses on the development of false smut disease of rice (Oryza sativa L.) were studied under field conditions at experimental area of Department of Plant Pathology, Punjab Agricultural University, Ludhiana during kharif 2013 and 2014. Five levels of nitrogen (40, 50, 60, 80 and 100 kg/acre) were tested for their effect on incidence and severity of false smut over two years at the same location. The results indicated that thedisease incidence, infected panicle and number of balls/plant were increased with increased nitrogen levels in tested rice cultivars viz PR114 and PR116. Disease severity (%) and unfilled grains (%) were also observed maximum at 100 kg nitrogen level in tested cultivars during both years.